Research on Train Autonomous Circumambulation System - QING Jianqiang; LEI Chengjian; LIANG Bo (Kongzhi Yu Xinxi Jishu)
This paper analyzes the disadvantages of traditional CBTC system in China’s urban rail transit, introduces the system architecture, principle and typical core functions of TACS (train autonomous circumambulation system), and gives a detailed comparison and analysis between TACS and traditional CBTC system.TACS is based on train to train and train to ground LTE-M-communication, which is based on train self-discipline, and characterized by train autonomous operation path, autonomous protection and autonomous operation adjustment. The trackside core control function is transplanted to the train. At the same time, TACS is highly integrated with vehicle network control, traction and braking system.Compared with the traditional CBTC system, the systen architecture of TACS is simpler and more reasonable, which greatly improves the utilization rate of line resource as well as the control accuracy. In the meantime, it reduces the project construction and operation costs by 20%~30%, and also reduce the project construction and commissioning cycles by 20%~30%. Besides, TACS is also more flexible in operation organization, which greatly improves the line operation efficiency, and the system is safer and more reliable.